Job Insecurity and Future Labour Market Outcomes - Wooden, M; McGuiness, S; Hahn, M; McGuinness, S (Melbourne, 2012)
This paper uses longitudinal survey data to test the degree to which measures of job insecurity are correlated with changes in labour market status. Three major findings are reported. First, the perceived probability of job loss is only weakly related to both exogenous job separations and subsequent transitions to unemployment and inactivity. Second, while fears of job loss tend to persist across time and job spells, they do so at a highly diminishing rate, suggesting that the impacts on other outcomes (such as psychological well-being) may be quite limited. Third, quit intentions are strongly correlated with both voluntary separations and transitions to alternative employment. The desire to quit, however, does not appear to diminish greatly across successive employment spells.
Melbourne Institute Working Paper Series
Keywords: Surveys and Survey Methodology; Employment -- Labour force status and attachment; Employment -- Security of employment; Surveys and Survey Methodology; Labour market; Surveys and survey methodology; Employment; Surveys and Survey Methodology; Labour force status and attachment; Security of employment; Employment and unemployment; Surveys and Survey Methodology